Plan de desarrollo Turístico para el cantón Chaguarpamba, provincia de Loja - Mora Largo, Juan Javier (2023)
This study “tourism development plan for the Chaguarpamba canton, province of Loja” has the general objective of create a tourism development plan that provide general guidelines for the tourism management of the canton. Thus, three specific objectives were established, the first: carry out a tourist situational diagnosis of the Chaguarpamba canton, Loja province, which allowed us to know the environmental, economic, social, cultural situation and the tourist demand and offer nothing that its tourist infrastructure is an aspect that need to be improved. With these results, the second objective was developed: Formulate tourism development proposals for the Chaguarpamba canton, province of Loja, where it began by identifying the local actors in the tourism sector then a SWOT analysis was carried out to indicate the existing problems in the place, and by Lastly, the problem sheet was applied in orders to identify its causes and stablish solutions, thus resulting in the following proposals aimed at training programs in tourism, elaboration of the ordinance project for tourism management in the territory, elaboration of a marketing plan, project of implementation for the implementation of a tourist signage and the strengthening of the tourist infrastructure of the “ Agua y Sol” With this, the last objective is given: To propose tourism development strategies for the Chaguarpamba canton, province of Loja, where different characteristics are detailed through matrices such as areas of action, activities, execution schedule, and budget so that the tourism development proposals previously described can be executed in the canton. Finally, conclusions and recommendations were raised, considering mainly as a conclusion that the canton has the tourist potential to be recognized as such, and among the recommendations it was proposed to minimize the existing problems by compromising the relevant public institutions and the residents of the canton.